The Activity-Induced Long Non-Coding RNA Meg3 Modulates AMPA Receptor Surface Expression in Primary Cortical Neurons - Tan, Men C.; Widagdo, Jocelyn; Chau, Yu Q.; Zhu, Tianyi; Wong, Justin J.-L.; Cheung, Allen; Anggono, Victor (Frontiers in Cellular Neuroscience, 2017)
Transcription of new RNA is crucial for maintaining synaptic plasticity, learning and memory. Although the importance of synaptic plasticity-related mRNAs is well established, the role of a large group of long non-coding RNAs (lncRNAs, > 200 bp) in long-term potentiation (LTP) is not known. In this study, we demonstrated the expression of a lncRNA cluster, namely Meg3, Rtl1-AS, Meg8 and Meg9, which is located in the maternally imprinted Dlk1-Dio3 region on mouse chromosome 12qF1, in primary cortical neurons following glycine stimulation in an NMDA receptor-dependent manner. Importantly, we also validated the expression of Meg3, Meg8 and Meg9 in the hippocampus of mice following cued fear conditioning in vivo. Interestingly, Meg3 is the only lncRNA that is expressed in the nucleus and cytoplasm. Further analysis revealed that Meg3 loss of function blocked the glycine-induced increase of the GluA1 subunit of AMPA receptors on the plasma membrane, a major hallmark of LTP. This aberrant trafficking of AMPA receptors correlated with the dysregulation of the PI3K/AKT signaling pathway and the downregulation of the lipid phosphatase PTEN. These findings provide the first evidence for a functional role of the lncRNA Meg3 in the intricate regulation of the PTEN/PI3K/AKT signaling cascade during synaptic plasticity in neurons.